Sex Metabolic Differences and Effects on Blood Coagulation Among Rats Exposed to Sodium Dehydroacetate - Chen, Xin; Hao, Fuxing; Zhang, Meng; Xiao, Jinzha; Zhao, Weiya; Zhao, Zeting; Zhang, Yumei (Frontiers in Pharmacology, 2021)
Sodium dehydroacetate (Na-DHA), a fungicide used in food, feed, cosmetics, and medicine, has been found to cause coagulation aberration accompanied by the inhibition of vitamin K epoxide reductase (VKOR) in the liver in rats. VKOR complex 1 (VKORC1) and VKORC1 like-1 (VKORC1L1) are two homologous VKOR proteins. Little information is available on the effect of Na-DHA on VKORC1L1 in the liver or VKORC1/VKORC1L1 in extrahepatic tissue and sex differences in Na-DHA metabolism. In the present study, after administration of 200 mg/kg Na-DHA by gavage, significant inhibition of VKORC1 or VKORC1L1 expression in tissues, as well as prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), were observed. The PT/APTT in the Na-DHA-exposed males were 1.27- to 1.48-fold/1.17- to 1.37-fold, while the corresponding values in the Na-DHA-exposed females were 1.36- to 2.02-fold/1.20- to 1.70-fold. Serum or tissue Na-DHA concentrations were significantly higher in females than in males. The pharmacokinetic parameters (t1/2, Cmax, AUC0 24h, and MRT0 24h) of Na-DHA in female rats were significantly higher than those in male rats. Furthermore, cytochrome P450 (CYP) activity was investigated using the cocktail probe method. The results revealed that Na-DHA exhibited an inductive effect on CYP1A2, 2D1/2, and 3A1/2 activities by changing the main pharmacokinetic parameters of probe drugs in male rats. However, no significant change in CYP2E1 activity was found. There were sex differences in the metabolism and coagulation in rats exposed to Na-DHA. The lower metabolism and higher blood Na-DHA concentration in females may be the reasons for higher coagulation sensitivity in female rats.